2020
DOI: 10.1080/0284186x.2020.1762927
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perspective in the context of proton beam therapy: summary of a Nordic workshop

Abstract: Introduction: On 15-16 November 2019, the Skandion Clinic in Sweden hosted the first Nordic workshop on 'Patients' perspective in proton beam therapy'. The workshop was conducted to describe and compare the patient care in PBT clinics in the Nordic countries and to initiate a collaboration, with the target to ensure patient participation and reduce the risk of inequity of access by lowering the barriers for accepting PBT in a distant clinic. The overarching aim of this workshop was to describe and compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…As facilities for PBT are nationally and globally relatively few, international collaboration is necessary to build the clinical evidence for the effect. A Nordic work-shop on the subject of “ Patients perspective in proton beam therapy” was held in Uppsala for the first time in autumn 2019, with members from Finland, Norway, Denmark and Sweden [ 32 ]. Future annual meetings are planned to collaborate within the field.…”
Section: Resultsmentioning
confidence: 99%
“…As facilities for PBT are nationally and globally relatively few, international collaboration is necessary to build the clinical evidence for the effect. A Nordic work-shop on the subject of “ Patients perspective in proton beam therapy” was held in Uppsala for the first time in autumn 2019, with members from Finland, Norway, Denmark and Sweden [ 32 ]. Future annual meetings are planned to collaborate within the field.…”
Section: Resultsmentioning
confidence: 99%
“…A centralized system (national network referring patients to two PT centers) has been implemented in Northern European countries. In this context, a recent workshop has shown that access to PT could imply for patients to be treated far away from home with a potential risk of inequity due to personal or practical barriers in a long-course of treatment [14] . In accordance with this finding, patients’ geographical challenges represented the main issue also according to the respondents to this survey.…”
Section: Discussionmentioning
confidence: 99%
“…In the Nordic European regions, two facilities centralized PT care. Ohlsson-Nevo et al reported the results of a workshop on patients’ perspectives in this context [14] . Among different analyzed factors, it has been highlighted that access to PT facilities could imply for patients to be treated away from home.…”
Section: Introductionmentioning
confidence: 99%
“…The paper by Ohlsson-Nevo et al describes the possibilities linked to systematic use of patient experiences on both individual and group level [5]. The participants concluded that inclusion of patients' perspectives in study protocols and systematic collection of patient-reported outcomes together with clinical outcomes is unique possibilities for future research on proton therapy.…”
mentioning
confidence: 99%